2014
DOI: 10.1111/ene.12524
|View full text |Cite
|
Sign up to set email alerts
|

Resource utilization and productivity loss in persons with spina bifida − an observational study of patients in a tertiary urology clinic in Germany

Abstract: The results indicate that persons with SB require a substantial amount of interaction with healthcare providers, as well as other healthcare-related resource use, both in the shorter and longer terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…For comparison, a German study evaluating hospital resource utilization within the spina bifida population reported an annual average of 14.8 hospital days per patient for hydrocephalus and non-hydrocephalus-related management. 27 Differences between HCRN centers regarding surgical outcomes were acknowledged and controlled for by study team members through statistical methods. Analysis of the variation in surgical outcomes between HCRN centers revealed that HCRN site had a statistically significant impact on the number of surgical revisions and hospital admission days due to revision at 1-, 3-, and 5-year outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, a German study evaluating hospital resource utilization within the spina bifida population reported an annual average of 14.8 hospital days per patient for hydrocephalus and non-hydrocephalus-related management. 27 Differences between HCRN centers regarding surgical outcomes were acknowledged and controlled for by study team members through statistical methods. Analysis of the variation in surgical outcomes between HCRN centers revealed that HCRN site had a statistically significant impact on the number of surgical revisions and hospital admission days due to revision at 1-, 3-, and 5-year outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in neurology occur across a broad front including neuro‐oncology, trauma, neuro‐otology and neurodevelopment. These areas also overlap with other specialist areas within the neurosciences.…”
mentioning
confidence: 99%